Ultra-high strength and ductility from rolling and annealing of a Ni-Cr-Co superalloy. (October 2018) - Slone, C.E.; Miao, J.; Mills, M.J.
Abstract: A new processing route is demonstrated for producing a nickel-based alloy with 1099 MPa tensile yield strength and 30% elongation. A chromium- and cobalt-rich commercial alloy was solution-annealed, cold-rolled, and aged at different temperatures and times to develop partially-recrystallized microstructures with ordered Ni3 (Al, Ti) γ′ precipitates. These were tested in uniaxial tension and compared to alloys given the same heat treatment without rolling to assess the contributions of different strengthening mechanisms. Orientation mapping showed the development of a modest 〈111〉 and 〈100〉 double-fiber texture. Scanning transmission electron microscopy also revealed the development of exceptionally large dislocation densities including wall structures. Graphical abstract: Unlabelled Image